The Improvement of Students Mathematical Problem Solving Ability by Implementing Cooperative Learning Model in Smp Tunas Pelita Binjai - Azrina Purba; Suci Ramadhani (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
This research is a quasi-experimental research with a pretest-posttest control group design. The purpose of this study was to determine the improvement of students' mathematical problem solving abilities using the STAD type cooperative learning model in class VIII of Tunas Pelita Binjai private Junior High School on algebraic operation material. The population in this study were the whole students of class VIII SMP Tunas Pelita Binjai and the sample was randomly selected, namely class VIII-1 (experimental class) and class VIII-2 (control class). The instrument used was a mathematical problem solving ability test instrument. The tests were carried out twice, namely at the beginning of learning (pretest) before receiving treatment and after receiving treatment at the end of learning (posttest). The instrument was confirmed to have fulfilled the validation and reliability requirements. The data analysis was performed using t-test. The finding of this study indicate that there is an improvement in students' mathematical problem-solving abilities using the STAD type cooperative learning model on the subject of algebraic operations significantly. The improvement was seen from the results of the gain score analysis, it was known that the average gain of the experimental class was in the moderate category (0.692) and the average gain of the control class was in the moderate category somehow lower than the experimental class (0.609). The aforementioned findings indicate that there was an improvement in the mathematical problem solving ability of the experimental class which was higher than the improvement in problem solving ability in the control class.